Resource Guide for Owners of Small Poutlry Flocks - Beyer, Scott (My University, 1998)
This publication lists hatcheries and supply sotres for producers to get a start with small poultry flocks.
MF2310_1998_01
Keywords: MF2310; Livestock; MF